Construindo uma política de formação para o orientador pedagógico da rede municipal de ensino de Presidente Prudente/SP: a parceria SEDUC e UNESP - Mendes, Cíntia Cristina Teixeira [UNESP]; Deák, Simone Conceição Pereira [UNESP]; Gomes, Alberto Albuquerque [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
In the organization of President Prudente Municipal Net of Education, the existence of a professional responsible for the organization of the teachers continued formation process at school unit is foreseen. Initially assigned as Nucleus Coordinator and later Pedagogical Counselor, this professional had its function ruled by the Statute of the Municipal Public Teaching of 1999, that defined the requirements for this function exercise, and by the Common Regiment of Municipal Schools of 2000, that defined as its primordial attribution the organization, coordination and counseling in the process of continued formation within the school unit. Under this scene, since the year of 2005, it was developed a framework whose basic axle was a diagnosis trying to identify the profile of the Pedagogical Counselors and teachers who operate County´s Education Net towards the organization and construction of the continued formation project in service at school units, whose horizon is the quality improvement of the pedagogical work of the above actors. To achieve this work, it was initially proceeded the reading, discussion and reflection of texts that approached the identity construction of this professional. Later, the indications of the Ministry of Education on the organization of the work of continued formation at the school, contained in the document called Reference for professors’ formation were presented (2002). Based on these indications, the group of Pedagogical Counselors of the County’s Education Net, in periodical meetings, has searched the construction of their own reference as a guideline to the construction of continued formation projects in service at school units.

En la organización de la Red Municipal de Educación de Presidente Prudente está prevista la presencia de un profesional responsable por la organización del proceso de formación continua de los profesores de la Unidad Escolar. Inicialmente denominado como Coordinador del Núcleo y posteriormente como Asesor Pedagógico, este profesional tiene su función reglamentada por el Estatuto del Magisterio Público Municipal de 1999, que define los requisitos para el ejercicio de la función y por el Regimiento Común de las Escuelas Municipales de 2000, que define como atribución principal la organización, coordinación y orientación del proceso de formación continua dentro de la unidad escolar. Dentro de este contexto, desde el año de 2005, realizamos un trabajo cuyo eje principal es un diagnóstico buscando identificar el perfil de los Asesores Pedagógicos y de los profesores que actúan en la Red Municipal con el intuito de organizar y construir el proyecto de formación continua para el servicio en las unidades escolares, cuyo horizonte es mejorar la calidad del trabajo pedagógico de los referidos autores. Para la realización del trabajo, se procedió inicialmente a la lectura, discusión y reflexión de textos que abordan la construcción de la identidad de este profesional. Posteriormente fueron presentadas las indicaciones del Ministerio de Educación sobre la organización del trabajo de formación continua dentro de la escuela, contenido en el documento denominado Referencial para la formación de profesores (2002). A partir de estas indicaciones, el conjunto de Asesores Pedagógicos da la Red Municipal, en reuniones periódicas buscaron la construcción de una referencia propia que se constituya como directriz para la construcción de los proyectos de formación continua para el servicio de las Unidades Escolares

Na organização da Rede Municipal de Ensino de Presidente Prudente é prevista a existência de um profissional responsável pela organização do processo de formação continuada dos professores na Unidade Escolar. Inicialmente designado como Coordenador de Núcleo e posteriormente Orientador Pedagógico, este profissional teve sua função regulamentada pelo Estatuto do Magistério Público Municipal de 1999, que definiu os requisitos para o exercício da função e pelo Regimento Comum das Escolas Municipais de 2000 que definiu como sua atribuição primordial a organização, coordenação e orientação do processo de formação continuada no interior da unidade escolar. Tendo em vista este cenário, desde o ano de 2005, foi desenvolvido um trabalho cujo eixo fundamental é um diagnóstico buscando identificar o perfil dos Orientadores Pedagógicos e dos professores atuantes na Rede Municipal com vista à organização e construção do projeto de formação continuada em serviço nas unidades escolares cujo horizonte é a melhoria da qualidade do trabalho pedagógico dos referidos atores. Para a consecução do trabalho procedeu-se inicialmente à leitura, discussão e reflexão de textos que abordavam a construção de identidade deste profissional. Posteriormente, foram apresentadas as indicações do Ministério da Educação sobre a organização do trabalho de formação continuada no interior da escola, contido no documento denominado Referencial para formação de professores (2002). A partir destas indicações, o conjunto de Orientadores Pedagógicos da Rede Municipal, em reuniões periódicas tem buscado a construção de um referencial próprio que se constitua como diretriz para a construção dos projetos de formação continuada em serviço nas Unidades Escolares.
Building continued education politics to pedagogical counselors of Presidente Prudente county education net: the partnership SEDUC and UNESP
Construyendo una política de formación para el asesor pedagógico de la red municipal de educación de Presidente Prudente/SP: convenio SEDUC y UNESP
Keywords: Pedagogical advisor; Continued formation; Pedagogical process; Asesor pedagógico; Formación continua; Proceso pedagógico; Humanas; Educação; Orientador pedagógico; Formação continuada; Processo pedagógico